DNA Methylation of POMC and NR3C1-1F and Its Implication in Major Depressive Disorder and Electroconvulsive Therapy - Maier, Hannah B.; Moschny, Nicole; Eberle, Franziska; Jahn, Kirsten; Folsche, Thorsten; Schülke, Rasmus; Bleich, Stefan; Frieling, Helge; Neyazi, Alexandra (Pharmacopsychiatry, 2023)
Introduction Precision medicine in psychiatry is still in its infancy. To establish patient-tailored treatment, adequate indicators predicting treatment response are required. Electroconvulsive therapy (ECT) is considered one of the most effective options for pharmacoresistant major depressive disorder (MDD), yet remission rates were reported to be below 50%.Methods Since epigenetics of the stress response system seem to play a role in MDD, we analyzed the DNA methylation (DNAm) of genes encoding the glucocorticoid receptor (NR3C1) and proopiomelanocortin (POMC) through Sanger Sequencing. For analysis, blood was taken before and after the first and last ECT from MDD patients (n=31), unmedicated depressed controls (UDC; n=19, baseline), and healthy controls (HC; n=20, baseline).Results Baseline DNAm in NR3C1 was significantly lower in UDCs compared to both other groups (UDC: 0.014(±0.002), ECT: 0.031(±0.001), HC: 0.024(±0.002); p<0.001), whereas regarding POMC, ECT patients had the highest DNAm levels (ECT: 0.252(±0.013), UDC: 0.156(±0.015), HC: 0.162(±0.014); p<0.001). NR3C1m and POMCm decreased after the first ECT (NR3C1: p<0.001; POMC: p=0.001), and responders were less methylated compared to non-responders in NR3C1(p<0.001).Discussion Our findings indicate that both genes might play a role in the chronification of depression and NR3C1 may be relevant for ECT response prediction.
Keywords: electroconvulsive therapy; epigenetics; DNA methylation; proopiomelanocortin; NR3C1; hypothalamic-pituitary-adrenal axis